REAKTUALISASI PEMIKIRAN AL-MAWARDI TENTANG ETIKA GURU - Yanuar Arifin (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2013)
In the contex of Islamic education, teacher is not someone who has a dutyto teach to the students. More than that, teacher is the spiritual father whogives a soul knowledge, leads the morals and make a right for bad behaviorwhich did by the students. But if we turn to the reality this day about adegradation of teacher’s ethic in any region, we perhaps little doubt thecredibility of teacher in having that duty and responsibility. Even, the senseof pesimism will soon if we see the sequence of news that makes the teacheras a main actor in any criminal and immoral behavior.That problem needs to be based on the importance of total comprehensiontoward the values of moral or ethic for a teacher who particularly willbe a need urgely. It is same as the view of al-Māwardī about the ethic ofteacher, which must have a several ethic, as tawadlu’ and avoid the attitudeof priding itself (‘ujub). Having ability to read the characteristic everystudents, avoid itself form shubbat, need to be qana’ah, sincere, and neverlose hope. That thought of al-Māwardī is sure very relevant with the worldof education in Indonesia at this moment.